Meningkatkan Pemahaman Masyarakat Untuk Hidup Sehat pada Masa Menopause - Sari, Dwi Rosella Komala (Universitas Muhammadiyah Surakarta, 2010)
Levels of estrogen in menopausal draktis will decrease. This situation is furtherfacilitate the development of coronary disease, dementia, osteoporosis, hypertensionand others. This service activities aimed at increasing public understanding aboutthe menopause, due to continued menopouse, and prevention of advanced menopausedue to the way a healthy lifestyle, balanced nutrition and regular exercise. The targetof this activity is the mother PKK Village Tuwak Wetan RT 01 RW 01 Gonilan Sukoharjototaling 35 people. This service activities performed by the method of counseling,which is done by the media approach with leaflets lecture and discussion. Before andafter the lectures conducted tests to determine the level of development of mothers.Results showed that activity after counseling the average value of the knowledge ofmothers increased from 5.45 and pretes value postes value becomes 7.04, the minimum value of 2 to 5, and the maximum value of 8 to 10. In addition, the category of mothers who have good knowledge increased from 19% to 66% and vice versa lessknowledgeable (not both) from 81% down to 34%. Thus, there is increasing knowledgeof mothers about the menopause, prevention of menopause due to go live by the patternof healthy, balanced nutrition and regular exercise.